Growth hormone-releasing hormone in the diagnosis and treatment of growth hormone deficient children. - Ross, R; Grossman, A; Besser, G; Savage, M (1986)
A growth hormone-releasing hormone (GHRH) has recently been extracted and synthesised, and appears to be identical to human hypothalamic GHRH. Immunoreactive GHRH is found in the venous blood of normal subjects and GH-deficient children, but is probably not hypothalamic in origin and therefore not important in GH regulation. GHRH is a potent specific stimulator of GH secretion in man, and provides a valuable diagnostic test in differentiating hypothalamic from pituitary causes of GH deficiency. Preliminary data suggests that GHRH may promote linear growth in some GH deficient children. GHRH may well prove an important alternative therapy for GH deficient children especially if depot preparations or intranasal administration prove effective.